Solicitation and Auditor Reporting Decisions. - Jeter, Debra C.; Shaw, Pamela Erickson (The Accounting Review, 1995)
Abstract Examines the question of whether direct solicitation rules affect auditors' decisions regarding the type of audit report to issue. Effect on audit quality by the removal of bans on direct uninvited solicitation; Associations between information dissemination, client-author alignment and auditor independence.